CASE REPORT: Chorangiophagus Parasiticus: A Rare Case Report - Ranjit Kangle (Journal of Krishna Institute of Medical Sciences University, 2012)
Malformations are common in twin pregency compared to singleton pregnancy. One such rare anomaly is Chorangiophagus parasiticus also known as twin to twin transfusion which is an asymmetric abnormality of monozygotic twins, where asymmetric twin survive by parasitisizing normal twin. It’s a rare condition with an incidence of 1 in 35.000 deliveries. We report such a case with complete autopsy findings.